ICASSP 2019 - 2019 IEEE International Conference on Acoustics, Speech and Signal Processing (ICASSP) 2019
DOI: 10.1109/icassp.2019.8683115
|View full text |Cite
|
Sign up to set email alerts
|

Tensor-ring Nuclear Norm Minimization and Application for Visual : Data Completion

Abstract: Tensor ring (TR) decomposition has been successfully used to obtain the state-of-the-art performance in the visual data completion problem. However, the existing TR-based completion methods are severely non-convex and computationally demanding. In addition, the determination of the optimal TR rank is a tough work in practice. To overcome these drawbacks, we first introduce a class of new tensor nuclear norms by using tensor circular unfolding. Then we theoretically establish connection between the rank of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
68
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(68 citation statements)
references
References 14 publications
0
68
0
Order By: Relevance
“…Lemma 2 shows that any TR unfolding X {i,l} obeys the strong matrix incoherence condition if the TR is strong incoherent. Note that [21] states that a TR unfolding obeys rank X {i,l} ≤ r i r i+l . We emphasize this inequality becomes equality under specific conditions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lemma 2 shows that any TR unfolding X {i,l} obeys the strong matrix incoherence condition if the TR is strong incoherent. Note that [21] states that a TR unfolding obeys rank X {i,l} ≤ r i r i+l . We emphasize this inequality becomes equality under specific conditions.…”
Section: Resultsmentioning
confidence: 99%
“…Eight algorithms are benchmarked on real-world data, including tensor ring nuclear norm minimization for tensor completion (TRNNM) [21], low rank tensor completion via alternating least square (TR-ALS) [18], simple low rank tensor completion via tensor train (SiLRTC-TT) [14], high accuracy low rank tensor completion algorithm (HaLRTC) [7], low rank tensor completion via tensor nuclear norm minimization (LRTC-TNN) [25], Bayesian CP Factorization (FBCP) for image recovery [26], smooth low rank tensor tree completion (STTC) [15] and the proposed one. These methods are based on different tensor decompositions, including CP, Tucker, t-SVD, HT, TT and TR decompositions.…”
Section: Numerical Experimentsmentioning
confidence: 99%
“…Our work is somewhat related to latent-norm based completion methods [37], [38] and Tensor-Ring based completion methods [32], [36], [39]. In [37], Tomioka et al proposed the latent nuclear norm by mode-k unfolding scheme (one mode versus the rest), and shown that it generalizes better than the overlapped nuclear norm [34] when only several modes are low-rank.…”
Section: Related Workmentioning
confidence: 99%
“…Rank-minimization based method is another type of approach to exploit the low-rank structure of incompleted tensor. Since the tensor rank minimization rank(•) is an NP-hard problem, a number of norms are defined as the convex surrogates of tensor rank, and the most commonly used ones are overlapped nuclear norm [34]- [36] and latent nuclear norm [37], [38]. In [34], the overlapped nuclear norm via Tucker rank was first proposed by assuming all modes are low-rank, while it performs poorly when the target tensor is only lowrank in a certain mode.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation